Unveiling the significance of Target of Rapamycin (TOR) signalling in grafting - Wenna Zhang; Lijuan Han; Yawen Huang; Jiawei He; Feng He; Yihan Dong (Vegetable Research)
Grafting is a widely employed horticultural technique that enables the combination of desirable traits from different plant species or cultivars. The success of grafting depends on various factors, including the strength of the seedlings, proper healing of the grafting junction, and the subsequent recovery of heterografted seedlings. In recent years, the target of rapamycin (TOR), a conserved protein kinase, has emerged as a key regulator of growth and development in plants. This perspective paper delves into the implications of TOR signalling in the grafting processes, including the role of the TOR signalling pathway in the regulation of seedling vigour prior to grafting, healing of graft junction and shoot-to-root communications. Particularly, we highlight the role of gibberellin and m5C modification in the regulatory network of TOR. However, further research is needed to unravel the precise molecular mechanisms underlying TOR's involvement in grafting and to optimize its application for improved grafting outcomes.